2016
DOI: 10.1186/s12909-016-0719-9
|View full text |Cite
|
Sign up to set email alerts
|

Attitude towards working in rural area and self-assessment of competencies in last year medical students: A survey of five countries in Asia

Abstract: BackgroundFive countries in Asia including Bangladesh, China, India, Thailand and Vietnam formed a network called Asia-Pacific Network for Health Professional Education Reforms (ANHER). This network collectively conducted a survey at the national level and at the institutional level (for medical, nursing and public health education). We also undertook an assessment of final year graduates from these schools on their attitudes, competencies and willingness to work in rural areas.MethodsPretested anonymous quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 11 publications
3
27
0
Order By: Relevance
“…Medical students whose parents were less educated were more likely to have intentions of choosing rural medical work than those whose parents received high-level education. However, a survey among medical students from five countries in Asia by Chuenkongkaew et al reported a contradictory finding that parents’ education was not significantly associated with their attitudes towards working in rural areas [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Medical students whose parents were less educated were more likely to have intentions of choosing rural medical work than those whose parents received high-level education. However, a survey among medical students from five countries in Asia by Chuenkongkaew et al reported a contradictory finding that parents’ education was not significantly associated with their attitudes towards working in rural areas [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qing et al [ 14 ], Huntington et al[ 5 ], and Van Wyk et al [ 39 ] reported that male students were more likely than female students to practice in rural areas in China, Nepal, and South Africa, respectively. However, Chuenkongkaew et al [ 11 ] found that male students were less positive about rural medical work than female students; Borracci et al [ 24 ], Zhang et al [ 28 ] and Puddey et al [ 12 ] demonstrated an insignificant association between the gender of medical students and their intentions. In addition, age and mother’s education were influencing factors of intentions of medical students with an urban background, whereas they were insignificant for rural medical students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are rich literatures on the willingness of medical students toward PHC or rural PHC career and associated determinants and motivations, from both developed countries and developing countries including China [9,12,14,15]. Determinants were classified as demographic, personal, social, intrinsic or extrinsic, monetary or non-monetary, experience and educational factors, etc.…”
Section: Introductionmentioning
confidence: 99%